Correlation Between Land-Use Change and Runoff Coefficients in Priority Watersheds: Analysis of BPS Statistical Data and Landsat Imagery (2014-2024) - Putu Doddy Heka Ardana; Wati Asriningsih Pranoto; Andre Kusuma Putra (CV. Get Press Indonesia, 2026)
Rapid urbanization within priority watersheds has triggered severe hydrological imbalances, necessitating a data-driven evaluation of land-use transformation. This study investigates the correlation between built-up area expansion and runoff coefficients () within the Upper Citarum Watershed, Indonesia, between 2014 and 2024. Utilizing a longitudinal quantitative design, the research integrates secondary statistical data from the Central Bureau of Statistics (BPS) with multi-temporal Landsat 8-9 OLI/TIRS satellite imagery. Spanning approximately 177,115 hectares, the analysis focuses on sub-watersheds with settlement growth exceeding 5% annually. Land Use and Land Cover (LULC) classification was executed using the Random Forest algorithm, while weighted runoff coefficients () were calculated through the Rational Method. Results indicate a profound shift in hydrological response, with the value escalating from 0.38 in 2014 to 0.59 by 2024, representing a 55% increase in peak discharge potential. Statistical validation reveals an exceptionally strong positive correlation () between BPS-documented building floor area growth and satellite-derived impervious surface expansion. These findings imply that current spatial planning and Building Permit (IMB) policies are insufficient to mitigate the loss of natural infiltration zones. The study concludes that the watershed has surpassed critical hydrological safety thresholds, necessitating a radical overhaul of Building Coverage Ratio (KDB) regulations and the mandatory adoption of Low Impact Development (LID) infrastructures. Future research should leverage high-resolution real-time sensors and artificial intelligence to enhance the precision of adaptive watershed management strategies.